2020
DOI: 10.1186/s10020-020-00228-5
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LUADT1 sponges miR-195 to prevent cardiac endothelial cell apoptosis in sepsis

Abstract: Background The oncogenic role of the newly identified lncRNA LUADT1 has been revealed in lung adenocarcinoma. It was reported that LUADT1 plays a critical role in multiple human diseases. This study was carried out to investigate the role of LUADT1 in sepsis. Methods Sixty patients with sepsis and sixty healthy volunteers were recruited for this study. Plasma samples were collected from all participants. Human primary coronary artery endothelial cells were also used in this study. The expression of Pim-1, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These studies are consistent with the possibility that several miRNA species may be "sponged", i.e., sequestered, by other non-coding RNAs [90] or mRNAs (the so-called "sponges"), potentially including actual miRNA-targets upregulated in sepsis [91]. Alternatively, these could be removed from (or exit) the blood circulation, in sepsis more than in other inflammatory conditions, globally affecting miRNA networks.…”
Section: Oxidative Stress and Micro-rna Pathways Relevant In Inflamma...supporting
confidence: 74%
“…These studies are consistent with the possibility that several miRNA species may be "sponged", i.e., sequestered, by other non-coding RNAs [90] or mRNAs (the so-called "sponges"), potentially including actual miRNA-targets upregulated in sepsis [91]. Alternatively, these could be removed from (or exit) the blood circulation, in sepsis more than in other inflammatory conditions, globally affecting miRNA networks.…”
Section: Oxidative Stress and Micro-rna Pathways Relevant In Inflamma...supporting
confidence: 74%
“…Overexpression of LUADT1 upregulated the expression of PIM1 , a target of miR-195. These findings indicated that overexpression of either LUADT1 or PIM1 would reduce the damage effects of miR-195 on LPS-induced apoptosis of cardiac endothelial cells ( 83 ). Yu et al ( 84 ) demonstrated that the drug Ulinastatin protected against LPS-induced cell hyperpermeability and apoptosis of cardiac microvascular endothelial cell (CMVECs) via downregulation of lncRNA MALAT1 and EZH2.…”
Section: Lncrna Involved In Sicd Among Various Cell Typesmentioning
confidence: 96%
“…Clinical treatment of SCM mainly includes intervening in septic shock, but a large amount of fluid resuscitation aggravates cardiac load. Studies have shown that autophagy [96,97] and noncoding RNA [98][99][100] are important in the pathogenesis of SCM, and interventions targeting autophagy and noncoding RNA have become a new direction for the treatment or study of SCM.…”
Section: Sepsismentioning
confidence: 99%